Trehalose and proline failed to enhance cold tolerance of the cowpea weevil, Callosobruchus maculatus (F.) (Col.: Bruchidae). (September 2021) - Masoumi, Z.; Shahidi Noghabi, S.; Izadi, H.
Abstract: The cowpea weevil, Callosobruchus maculatus (F.) (Col.: Bruchidae) is a cosmopolitan field-to-store pest ranked as the major post-harvest pest of cowpea in tropical regions. The cold tolerance of an insect species can vary as a result of abiotic features including food resources. In this study, C. maculatus larvae were fed with proline and trehalose (10, 20, and 40 mmol) treated cowpea seeds to determine the effects of these potential cryoprotectants on the supercooling (SCP) and cold hardiness of the upcoming adult beetles. The SCPs of the control, proline-fed and trehalose-fed adults non-significantly changed from −18.2 °C for the control to −17.2 °C for trehalose-fed adults. The cold hardiness (24 h at 0, -5.0, −7.5, −10.0, and −12.5 °C) of the adults was almost the same for control and treatments. Median lethal times (LT50 ; lethal time for 50% mortality) were 6.3, 6.0, and 5.4 h, respectively. Moreover, feeding the larvae with proline and trehalose-treated seeds did not affect the proline and trehalose contents of the adult beetles. Our results showed that C. maculatus could not tolerate subzero temperatures well above their SCP, indicating that this species might be a chill-susceptible insect. Highlights: Effects of the diets augmented with trehalose and proline on cold tolerance of Callosobruchus maculatus were studied. Diet augmentation had no significant effect on the supercooling point and cold tolerance of the pest. Augmentation of the diet did not result in the accumulation of trehalose and proline in the beetle total body fluid. The supercooling point (SCP) of the pest was approximately -18.0 °C. The pest is chill susceptible and 6 h exposure to subzero temperatures (-10 °C) is sufficient to kill it.